Fruit ripening/scald relationship in apple - Gutierrez, Maria Soledad <1978> (Alma Mater Studiorum - Università di Bologna, 2014)
The ripening stage of apple fruits at harvest is the main factor influencing fruit quality during the cold storage period that lasts several months and give rise to physiological disorders in fruits of susceptible cultivars. In particular, superficial scald is connected to α-farnesene oxidation, leading to fruit browning. Therefore, the assessment of the optimal ripening stage at harvest is considered to be crucial to control the overall quality, the length of storage life and the scald incidence. However, the maturity indexes traditionally used in the horticultural practice do not strictly correlate with fruit maturity, and do not account for the variability occurring in the field. Hence, the present work focused on the determination of apple fruit ripening with the use of an innovative, non-destructive device, the DA-meter. The study was conducted on ‘Granny Smith’ and ‘Pink Lady’ cultivars, which differ in scald susceptibility. Pre- and post- harvest ripening behavior of the fruits was studied, and the influence of ripening stage and treatments with 1-MCP were evaluated in relation to scald development and related metabolites. IAD was shown to be a reliable indicator of apple ripening, allowing cultivar-specific predictions of the optimal harvest time in different growing seasons. IAD may also be employed to segregate apple fruits in maturity classes, requiring different storage conditions to control flesh firmness reduction and scald incidence. Moreover, 1-MCP application is extremely effective in reducing superficial scald, and its effect is influenced by fruit ripening stage reached at harvest. However, the relation between ethylene and α-farnesene was not entirely elucidated. Thus, ethylene can be involved in other oxidative processes associated with scald besides α-farnesene regulation.